PHYSICO-CHEMICAL PROPERTIES OF REFINED OIL BASED ON MATURITY LEVEL AND DRYING TIME OF NUTMEG MACE (MYRISTICA FRAGRANS HOUTT) - Mamuaja, Christine F; Lumuindong, Frans; Paat, Frangky Jessy; Kaurow, Welly A.; Oessoe, Yoakhim J.E.; Rorong, Frangky (Journal of Agriculture, 2023)
This research aims to study and determine the level of full maturity and the appropriate and best drying time for nutmeg mace so that a high yield of mace oil is produced with physico-chemical properties that meet Buenther's criteria. Ripe nutmeg will produce good quality nutmeg and mace when used as spices for export. Apart from that, old nutmeg mace can still be used for its essential oil because the oil content is still quite high. To get nutmeg oil from the fruit when it is young, you can also get mace which has a high level of oil content. The water content in mace is quite high so it is easy for mold to grow and will affect the oil yield and possibly also the physico-chemical properties of the oil. This research is a factorial experiment using a Completely Randomized Design (CRD) consisting of two factors. Factor A, namely the maturity level of mace, consists of two levels, namely full young and old mace. Factor B is the drying time of mace with four levels, namely 0, 8,16 and 24 hours. Each treatment was repeated three times. The oven drying temperature was 40° C and distillation was carried out for 20 hours. The results of the research for each level of mace maturity gave significant differences to the yield, specific gravity, refractive index, optical rotation and acid number of the refined oil, while the length of drying of the mace gave a real difference to the physico-chemical properties of the mace oil. The best results obtained were young mace which was dried for 24 hours with the following characteristics, full water content of 6.77%, mace oil yield of 12.8889 ml/100 grams of material, specific gravity of mace oil 0.9255; full oil refractive index 1.4871; The optical rotation of the oil is (+) 6.3433 and the acid number of mace oil is 2.29.